Local Scouring Visualization of Bed Channel Surface in Hydraulic Structure Using Surfer - Paramadita, Tifarah Dayansabila; Azarine, Nadia; Azhar, Aburizal; Riyanto, Didit Puji (Jurnal Teknik Sipil dan Perencanaan, 2022)
Abstract. Water flowing in the river causes a scouring event that occurs at the bed channel. The existence of scouring will increase along with changes in the geometry of the river and obstacles such as the weir which are followed by local scouring around the weir. Local scouring often occurs downstream end of weir sill which weakens its construction. Scouring measurement was conducted to monitor the pattern of scouring that occurs. By using Surfer software, the scouring visualization through the Data Grid and 3D Surface can be seen. In this research, scour monitoring in the laboratory using open channels (flume) and MDO weir with fine aggregate material as the basis of the channel. The retrieval of scouring data was performed after installing fine aggregate and three times variations of flow discharge, then the data were processed using Surfer. The first flow used water level +3.50 with the material carried at 3.77%. The second flow used water level +4.50 with the material carried at 11.16%. The third flow used water level +5.70 with the material carried at 25.46%. So with the continuous method, the total material carried at 36.27% is equivalent to 12575.77 cm3.